Pengaruh Kurs terhadap Inflasi dan Harga Saham: Studi Kasus di Bank BTN - cahya cahya (Accounting and Finance Studies, 2021)
This study aims to determine the effect of the exchange rate and inflation on the stock price of Bank BTN. This study uses quantitative methods. The population in this study is Bank BTN because this research is a case study. The choice of Bank BTN was due to the lack of research on exchange rates, inflation, and related stock prices. This study uses data from Bank BTN's financial statements obtained from the IDX.co.id page. This study uses the period from the third quarter of 2010 to the second quarter of 2020. This study uses linear regression analysis because it uses one independent variable and two dependent variables. The independent variable in this study is the exchange rate. The dependent variables in this study are inflation and stock prices. The results showed that the exchange rate had a significant positive effect on inflation and stock prices of Bank BTN. The results of this study can be used as a reference for making stock purchase decisions, especially at Bank BTN. An overview of further research is also presented here.